GLYCOSYLATION DISORDER SYNDROME TYPE 1b: DIAGNOSTICS AND TREATMENT - Yu.S. Akoev; A.V. Migali; N.V. Zhurkova; O.B. Kondakova; E.A. Roslavtseva; A.R. Pinaeva; V.A. Skvortsova; I.I. Migali (Педиатрическая фармакология)
The article highlights the medical case of a rare hereditary disease — glycosylation disorder syndrome type 1b, unique for our country. This syndrome is referred to the heterogeneous group of the congenital diseases characterized by the disorder of glycoprotein synthesis as a result of the defects N or O glycosylation. Manifestations of the disease are protein losing enteropathy and severe developmental delay, hypoglycemia, co agulopathy (thrombosis), liver injury. glycosylation disorder syndrome type 1b differs from other types of this group absence of the neurologic semiology and efficiency of therapy by mannose.Key words: glycoproteins, glycosylation disorders, manifestations, mannose, children.